Effect of Drying Kinetics on the Quality of Dried 𝙂𝙧𝙖𝙘𝙞𝙡𝙖𝙧𝙞𝙖 𝙨𝙖𝙡𝙞𝙘𝙤𝙧𝙣𝙞𝙖 (C. Agardh) Dawson - Junlakan, Wannapit; Yamsaengsung, Ram (Burapha Science Journal, 2024)
Background and Objectives : People of Koh Samui in Surat Thani Province often bring Gracilaria Salicornia (C. Agardh) Dawson that is in large quantities during the season to be blanched and frozen to preserve raw materials before being processed by drying methods. The purpose of this research was to study the effect of drying kinetics on the physical and chemical quality of dried Gracilaria Salicornia (C. Agardh) Dawson. Methodology : Drying experiments were carried out at drying temperatures of 60, 70 and 80oC using six different drying methods were a vacuum drying (VD), a blanching before (B-VD) vacuum drying, and a freezing and thawing at room temperature before vacuum drying (F-VD), a hot air drying (CD), a blanching before hot air drying (B-CD) and a freezing and thawing at room temperature before hot air drying (F-CD). Main Results : VD at 80oC of algae showed more rehydration, less color change, higher total phenolic values, higher tannin values, and higher -carotene values compared to other drying methods. Consequently, the VD at 80oC was suggested as the best drying condition. Conclusions : VD at 80oC of algae showed shorter drying, higher values of the effective moisture diffusivity and lower values of activation energy. The high moisture diffusion at the short drying time creates a large amount of pores inside the product, which corresponds to a high rehydration ratio. Moreover, the short drying period resulted in the high retention of total phenolic compounds, tannins, chlorophyll A and - carotene in the product. The suitable thin layer model for drying of algae with VD at 80oC was two-term exponential.